Prognostic factors in patients with recurrent or metastatic retroperitoneal leiomyosarcoma. (June 2015) - Li, Qian; Zhuang, Rongyuan; Zhu, Jun; Lu, Weiqi; Hou, Yingyong; Liu, Ju; Zhang, Yong; Wang, Yan; Liu, Tianshu; Wang, Zhiming; Zhou, Yuhong
ABSTRACT : Aims: Factors that predict the prognosis of patients with recurrent or metastatic retroperitoneal leiomyosarcomas after treatment are uncertain.Materials & methods: Clinical and pathological data on 22 patients with retroperitoneal leiomyosarcomas who were treated by a multidisciplinary abdominal soft-tissue tumor group were analyzed retrospectively to identify prognostic factors for their progression-free survival (PFS).Results & conclusion: The median PFS in the 22 patients was 9 months. Microvessel density in tumor tissues, which was evaluated via CD34 expression in 16 cases, and the presence of metastasis on admission were both found to be correlated with PFS in a Kaplan–Meier analysis, but not in a multivariate analysis. The multivariate analysis did, however, show that complete resection of tumors and the FNCLCC (Fédération Nationale des Centres de Lutte Contre Le Cancer) disease grade were independent factors predicting PFS.